Peranan Tuhapeut dalam Rangka Menciptakan Harkamtibmas - A. Ichsan (Law Faculty of Universitas Bandar Lampung, 2012)
In societal life not rarely experience of trouble of Kantibmas the including criminal in the middle of society as one of the way of accomplishment of requirement like robbing, stealing, threaten with weapon. Because of society citizen have stick habit do not impinge regulation of custom and religion. What share in teaching religion teaching and custom is Tuhapeut. At Recently role of this tuhapeut experience of resistance so that kriminal impress to go up sub-province of Simeulue. Problem of this research is how role of Tuhapeut in order to creating Harkamtibmas? Role Of Tuhapeut To Prevent Kriminal In Order To Creating Harkamtibmas:Â Result of research show society citizen do not entangle all tuhapeut in solving of the problem of in Countryside because of all Tuhapeut figure authority do not at epoch first, this happened because shifting value him civilization of human being, because of there are some all Tuhapeut have made many mistake in the middle of society, during the time do not be effective so its Organization, all Tuhapeut do not have strong authority only just public spirited so that in its performance impress justly to come from, this happened because less care attention him of governmental side in this case Lawcourt of SyariAh less effective socialize to society.